A Multi-Regional Analysis of AMS and Radiometric Dates from Carbonized Food Residues - J. P. Hart; Lovis, W. A. (Midcontinental Journal of Archaeology, 2007)
Accelerator Mass Spectrometry (AMS) is increasingly employed to date encrusted carbonized food residues on prehistoric pottery sherds, particularly in regions where other datable material is absent or scarce, or where such materials lack good association with objects of chronological interest. The accuracy of AMS dating of residues has recently been questioned in Europe and North America, with skepticism directly or indirectly attributed to the presence of carbonate rich bedrock, a freshwater carbonate reservoir resulting from association with such bedrock, or the cooking of aquatic resources such as mollusk or fish engaged in the uptake of older carbonates. It is argued that carbonized food residues from such contexts or resources are expected to display older apparent ages than dates on other materials. We evaluate this proposition through hypotheses assessing the accuracy and internal consistency of a broad range of data from the northeastern and midwestern United States. We statistically assess dates from 25 site components where either both dates on residue and context dates on other materials have been obtained. Of the 70 dates on residue tested, only 5.7 percent are considered inconsistent with their respective context dates. We also test for consistency 46 dates on residues from 14 site components lacking context dates. Of these, only 4.5 percent are considered internally inconsistent with expectations at the site or regional level. At present, we conclude that AMS dating of residues provides results consistent with those of other datable materials.
Keywords: AMS dating; cooking residues; Fresh water reservoir effect